2011
DOI: 10.1002/dvdy.22778
|View full text |Cite|
|
Sign up to set email alerts
|

Deficiency in crumbs homolog 2 (Crb2) affects gastrulation and results in embryonic lethality in mice

Abstract: The Crumbs family of transmembrane proteins has an important role in the differentiation of the apical membrane domain in various cell types, regulating such processes as epithelial cell polarization. The mammalian Crumbs protein family is composed of three members. Here, we inactivated the mouse Crb2 gene with gene-targeting techniques and found that the protein is crucial for early embryonic development with severe abnormalities appearing in Crb2-deficient embryos at late-gastrulation. Our findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 69 publications
6
62
1
5
Order By: Relevance
“…One important player in the EPP is Crumbs (Crb), originally identified in Drosophila. Loss of function of Drosophila crb causes loss of apico-basal polarity and tissue integrity in many embryonic epithelia (Grawe et al, 1996;Jürgens et al, 1984;Tepass, 1996;, and comparable phenotypes are observed in mouse embryos lacking either Crb2 or Crb3, two of the three mammalian Crb genes (Whiteman et al, 2014;Xiao et al, 2011). These results highlight the functional conservation from flies to mammals.…”
Section: Introductionmentioning
confidence: 89%
“…One important player in the EPP is Crumbs (Crb), originally identified in Drosophila. Loss of function of Drosophila crb causes loss of apico-basal polarity and tissue integrity in many embryonic epithelia (Grawe et al, 1996;Jürgens et al, 1984;Tepass, 1996;, and comparable phenotypes are observed in mouse embryos lacking either Crb2 or Crb3, two of the three mammalian Crb genes (Whiteman et al, 2014;Xiao et al, 2011). These results highlight the functional conservation from flies to mammals.…”
Section: Introductionmentioning
confidence: 89%
“…In Drosophila embryos, loss of crb function results in embryonic lethality, caused by the breakdown of many epithelia (Grawe et al, 1996;Tepass, 1996;. Comparable phenotypes are observed in mouse embryos lacking Crb2 or Crb3, two of the three mammalian Crb genes (Charrier et al, 2015;Szymaniak et al, 2015;Whiteman et al, 2014;Xiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CRB2 distribution overlaps that of CRB1, but CRB2 is also found in other organs such as kidneys (15). CRB2 is required for retinal integrity and for gastrulation of mouse embryos (16,17). CRB3 is widely expressed in epithelial tissues and exists as two isoforms, namely, CRB3A and CRB3B (18,19).…”
mentioning
confidence: 99%